2017
DOI: 10.3177/jnsv.63.277
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Oxidative Stress by Antioxidant Supplementation Does Not Limit Muscle Mitochondrial Biogenesis or Endurance Capacity in Rats

Abstract: SummaryThe objective of the present study was to analyze the activation and expression patterns of upstream and downstream factors of PGC-1a to determine whether antioxidant (AO) supplementation inhibits mitochondrial biogenesis in skeletal muscles as an adaptation to endurance training, as well as to analyze changes in endurance capacity based on such findings. For this objective, 24 male Sprague-Dawley (SD) rats were allocated into 4 groups (vehicle-sedentary, V-Sed; vehicle-exercise, V-EX; antioxidant-seden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Antioxidants are substances that contribute to relieving the effects of stress and oxygen deprivation caused by exercise by reducing free radical reactions. 38 The portion of the consumed grains group showed a higher mean in the endurance sport. This result was in line with the components of carbohydrate intake where there were differences between the two groups.…”
Section: Resultsmentioning
confidence: 90%
“…Antioxidants are substances that contribute to relieving the effects of stress and oxygen deprivation caused by exercise by reducing free radical reactions. 38 The portion of the consumed grains group showed a higher mean in the endurance sport. This result was in line with the components of carbohydrate intake where there were differences between the two groups.…”
Section: Resultsmentioning
confidence: 90%
“…Muscle extracts were prepared and Western blotting was performed as described previously [ 40 ]. Blots were probed with the following antibodies: Akt, P-Akt, mTOR, P-mTOR, MuRF-1, Atrogin-1 (Bio-Rad, CA, USA), and β-actin (Sigma, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies have also shown that 4 to 14 weeks of aerobic training with antioxidant intake blunted training-induced increases in cytochrome oxidase and CS activity, mitochondrial transcription factor A (TFAM), CYT-C, GPx, glutathione reductase, SOD, PGC-1, NRF-1, and NRF-2 [118,[128][129][130], although other research has shown no effect on markers of training adaptations such as mitochondrial respiratory capacity, and CYT-C, COX-I, COX-IV, CS, NRF-1, or PGC-1 protein content [130][131][132][133].…”
Section: Vitamins C and Ementioning
confidence: 99%
“…The reason for these divergent findings, particularly in the animal research, may be due to variations in dosing, exercise protocols, and baseline levels of endogenous antioxidants. The amount of antioxidant provided has varied more than 10-fold [128,134], exercise type has included both running and swimming, and the duration of training sessions has ranged from 30 min to six hours per day [132][133][134]. Potential redundancies in the adaptation process must also be considered.…”
Section: Vitamins C and Ementioning
confidence: 99%